2018
DOI: 10.1007/s10151-018-1820-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of blood diagnostic markers in colorectal cancer

Abstract: The purpose of this systematic review was to compare the diagnostic ability of blood markers for colorectal cancer (CRC). A systematic review of the literature for diagnostic blood markers for primary human colorectal cancer over the last 5 years was performed. The primary outcome was to assess the diagnostic ability of these markers in diagnosing colorectal cancer. The secondary outcome was to see whether the marker was compared to other markers. The tertiary outcome was to assess diagnostic ability in early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 61 publications
(82 reference statements)
2
88
0
Order By: Relevance
“…The cluster analysis revealed that only miR-31 was significantly upregulated in non-MSI CRC specimens with the BRAF V600E mutation (sample Id, 341), while miR-429, -375, -200a, -200b and -192 were downregulated compared with that in the other CRC phenotypes, such as CRCs with wild-type BRAF. Generally, molecules that are significantly and specifically upregulated in tumors are useful for screening those tumors via liquid biopsy or other screening tools (26). Therefore, subsequent analyses focused on miR-31 as a candidate prognostic biomarker in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cluster analysis revealed that only miR-31 was significantly upregulated in non-MSI CRC specimens with the BRAF V600E mutation (sample Id, 341), while miR-429, -375, -200a, -200b and -192 were downregulated compared with that in the other CRC phenotypes, such as CRCs with wild-type BRAF. Generally, molecules that are significantly and specifically upregulated in tumors are useful for screening those tumors via liquid biopsy or other screening tools (26). Therefore, subsequent analyses focused on miR-31 as a candidate prognostic biomarker in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…microRNAs (miRNA/miR) have been revealed as candidates in tumor progression in various cancer types, and changes in their expression levels are consequently being investigated with the purpose of identifying clinical biomarkers (3)(4)(5)(6)(7)(8)(9). miRNAs constitute a class of small, non-coding RNA molecules, [18][19][20][21][22][23][24][25][26][27] nucleotides in length that function as post-transcriptional regulators of gene expression, either serving as oncogenes or tumor suppressor genes (10,11). In CRC, several miRNAs are aberrantly expressed and target genes downstream of epidermal growth factor receptor (EGFR) signaling; for example, miR-143 and -145 target KRAS and BRAF proteins, respectively (12).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, this aim can be achieved with a noninvasive and inexpensive method, using readily available biological samples, including serum and feces (37). At present, potential molecular biomarkers for CRC diagnosis are broadly divided into the following four groups: Nucleic acids, cytokines, antibodies and proteins (38). Blood-based markers in current use, including CEA and CA19-9, are suitable for surveillance and for monitoring responses to treatment; however, they exhibit low sensitivity and specificity, ranging between 40 and 70%, and 73 and 90%, respectively, which makes them unsuitable as screening or diagnostic markers (39).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the in vitro diagnostic (IVD) of tumor markers is the focal point of research in cancer detection. From the first genetic model of colorectal tumorigenesis proposed by Fearon and Vogelstein in 1990 [2] until today, when it is known that the transformation of adenoma to carcinoma is driven not only by genetic alteration but epigenetic alterations [3], many tumor markers have been proposed to describe this complex process [4][5][6][7][8][9][10][11]. The most recent findings regarding molecular events along the adenoma-carcinoma sequence urgently demand the development of detection methodologies and strategies that allow the simultaneous determination of tumor markers of different molecular nature with simple protocols and suitable for point-of-care (POC) testing.…”
Section: Introductionmentioning
confidence: 99%